Expression of cell markers and transcription factors in the avian retina compared with that in the marmoset retina - Haverkamp, Silke; Albert, László; Balaji, Vaishnavi; Němec, Pavel; Dedek, Karin (The Journal of comparative neurology, 2021)
In the vertebrate retina, amacrine and ganglion cells represent the most diverse cell classes. They can be classified into different cell types by several features, such as morphology, light responses, and gene expression profile. Although birds possess high visual acuity (similar to primates that we used here for comparison) and tetrachromatic color vision, data on the expression of transcription factors in retinal ganglion cells of birds are largely missing. In this study, we tested various transcription factors, known to label subpopulations of cells in mammalian retinae, in two avian species: the common buzzard (Buteo buteo), a raptor with exceptional acuity, and the domestic pigeon (Columba livia domestica), a good navigator and widely used model for visual cognition. Staining for the transcription factors Foxp2, Satb1 and Satb2 labeled most ganglion cells in the avian ganglion cell layer. CtBP2 was established as marker for displaced amacrine cells, which allowed us to reliably distinguish ganglion cells from displaced amacrine cells and assess their densities in buzzard and pigeon. When we additionally compared the temporal and central fovea of the buzzard with the fovea of primates, we found that the cellular organization in the pits was different in primates and raptors. In summary, we demonstrate that the expression of transcription factors is a defining feature of cell types not only in the retina of mammals but also in the retina of birds. The markers, which we have established, may provide useful tools for more detailed studies on the retinal circuitry of these highly visual animals.
Keywords: Animals; Female; ganglion cells; transkripční faktory; amacrine cells; Retina; ženské pohlaví; druhová specificita; marmoset retina; Species Specificity; Transcription Factors; amakrinní buňky; Amacrine Cells; Columbidae; Callithrix; Male; starburst amacrine cells; retina; zvířata; mužské pohlaví; transcription factor; fovea; cell type